Two decades of re-aligning mundane entrepreneurship in Cuba - Scarpaci, Joseph L.; Henken, Ted A.; Ritter., Archibald R. M. (Economía Sociedad y Territorio, 2016)
We examine how small entrepreneurs perceive their changing internal and external environments in Cuba, a country with a highly regulated yet emerging entrepreneurial class. We build on the concept of everyday exchange or mundane entrepreneurship, originally developed as a lens to understand non-state actions in the former USSR, and apply it to contemporary Cuba in the post-Soviet era. Our socially situated case of entrepreneurship in Cuba identifies how entrepreneurial behavior is sustained outside the contexts of the market. The result is a realignment in which contemporary entrepreneurship on the island shares important similarities with the Soviet blat system, while it also exhibits attributes that are unique to the Cuban case.